Islam in the West : perceptions and reactions - Ata, Abe W; Ali, Jan A. (Oxford University Press, 2018)
This book focuses on the way Muslims and mainstream societies in the West, especially in America, Australia, and Europe, perceive each other. It focuses on the meaning of being a Muslim in a multicultural, multi-religious, and technologically developed world.